Mitigating the underlying factors leading to gender inequality in the design of construction projects in the UAE - ALMULLA, FATEMA MOHAMMED EBRAHIM HASAN (2018)
Understanding gender inequality is the first step of addressing the evident issue that resides within our society, workplace, and world. In this study, we are looking at gender inequality in the UAE’s construction sector, and taking it a step further by looking at underlying factors that aid to gender inequality in the design of construction projects in the UAE. In this research we are using mixed method methodology using grounded theory for our research. The approach of this study begins with a literature review of gender inequality in different sectors such as construction and design of construction projects, faced by women around the world covered by research done by different scholars. The research was compared contrasted and analyzed. Then the conceptual framework was established which then allowed for the research questions to be put in place as well as the hypotheses. The next step was to go ahead with the quantitative research methodology and then with the qualitative research methodology. Once the research was conducted the findings were analyzed, compared and contrasted to the hypotheses, in which it was discovered that there is a connection with two of the independent factors which were the correlation of a company’s bias towards men in relation to how women perform at the workplace and socio-cultural norms in the design of construction projects in the UAE. The results also discovered that there was no connection of a company’s bias towards men when it came to the number of women that joined the construction sector or how a company’s competencies are measured. The qualitative research came about four themes that influence gender inequality which were education, family, socio-cultural and the organization itself. The paper concludes with the take away from the research and mentions of some of the limitations the research faced as well as some recommendations on the research and how to further the study on gender inequality in the design of construction projects in the UAE.